Effectiveness and safety of ultrasound-guided stellate ganglion block in C57BL/6 mice - Liu, Xiaohong; Wu, Xuyang; Wu, Liang; Lin, Fengyi; Yan, Jingjia; Zhang, Jiuyun; Zheng, Xiaochun; Chen, Xiaohui; Lu, Qingwang (Frontiers in Medicine, 2025)
ObjectivesStellate ganglion block (SGB) is a unique anesthetic procedure distinguished by rapid onset, precise effects, and repeatability. The advent of ultrasound guidance has markedly increased the accuracy and safety of this technique, providing a novel approach for nerve blockade in model animals. This study aimed to evaluate the efficacy and safety of ultrasound-guided SGB in C57BL/6 mice, a strain commonly used in biomedical research because of its stable genetic characteristics and well-documented immune responses.MethodsA total of 8–10-week-old C57BL/6 mice were used in this study and were divided into three groups: the control group, the SGB-R group (right side), and the SGB-L group (left side). The SGB-R and SGB-L groups received an injection of 0.25% ropivacaine solution in a volume of 0.08 mL, whereas the control group was administered an equivalent volume of saline. To evaluate the efficacy of the procedure, we monitored the incidence of Horner’s syndrome, heart rate fluctuations, changes in carotid artery flow velocity and diameter, and temperature variations in the affected upper limb. Additionally, we used 3D CT imaging to precisely identify the needle tip position and the diffusion range of the local anesthetic. Simultaneously, we documented the associated complications, including brachial plexus block, hematoma, respiratory distress and mortality, to assess the safety of the procedure.ResultsAmong the SGB-treated mice, 100% presented with Horner’s syndrome. Compared with preintervention levels, the SGB-R and SGB-L groups presented significant decreases in heart rate, increases in carotid artery diameter, increased blood flow velocity, and elevated limb temperature on the blocked side after SGB intervention. Compared with the Con group, the SGB-R and SGB-L groups presented significantly greater carotid artery diameter and blood flow velocity, as well as notable increases in limb temperature. Importantly, no major postsurgical complications, such as brachial plexus injury, hematoma, respiratory distress, or mortality, occurred in any of the groups.ConclusionThis study presents a methodological blueprint for the implementation of ultrasound-guided SGB in C57BL/6 mice, demonstrating its potential effectiveness and safety. The newly established SGB model significantly enhances stability and minimizes potential complications. Compared with traditional techniques, this method offers superior applicability for SGB-related research.